On the Issue of Civil Liability for Inadequate Provision of Medical Services - KIZDARBEKOVA, Antonina S.; PRUDNIKOVA, Marina Yu.; NURZHANOVA, Aliya S. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The relevance of the researched problem is determined by the fact that until recently, problems of protecting the rights of the patient were researched in science extremely fragmentary, and the responsibility of medical workers in the event of their violation was based on bringing the perpetrators to disciplinary, less often to criminal and administrative responsibility. Thus, the article is aimed at exploring a new approach in the implementation of the constitutional right of citizens to health care, which has resulted from a change in the status of health authorities. The leading approach to the study of this problem is a descriptive method that allows identifying and analyzing in detail the specifics of the civil liability of doctors for inadequate medical services to patients. The analysis of the positions developed in the Kazakhstan and Soviet scientific thought on the specified circle of problems is carried out. The materials of the article suggest practical significance for university professors of legal specialties.